Development of magnetic fabrics during hydrothermal alteration in the Soultz-sous-Forêts granite from the EPS-1 borehole, Upper Rhine Graben - Just, Jana; Kontny, Agnes; Wall, Helga de; Hirt, Ann M.; Martín-Hernández, Fatíma (Magnetic fabric, 2004)
Skip to Next Section - The Variscan, magnetite-bearing Soultz-sous-Forêts granite is found between 1420 and 2230 m of the EPS-1 borehole situated in the Upper Rhine Graben (France). Our study focuses on the changes of magnetic properties that occur during the progressive hydrothermal alteration and fracturing of the Soultz granite after emplacement. The magnetic susceptibility (κ) of the granite is between 10 and 80 × 10−3 SI, and suggests that ferrimagnetic minerals are the primary carrier. During cooling and later tectonic and hydrothermal overprints, including the formation of the Rhine Graben, the granite was deformed under brittle conditions and partially altered by hydrothermal fluids. Along with this fluid activity, oxidation of magnetite to hematite occurred and reduced κ (< 1 × 10−3 SI). AMS analysis on oriented samples documents the history of progressive transformation from primary magmatic fabric to tectonic fabric during hydrothermal alteration and faulting. The fresh granite with multidomain magnetite grains shows sub-horizontal magnetic foliations and randomly oriented magnetic lineations within the foliation plane. This fabric is similar to the magmatic fabric reflected by biotite. Transformation of the magnetic fabric started with localized magnetite oxidation along NW-SE oriented micro-cracks, which are probably associated with a late-magmatic alteration (stage I). Elongated and co-aligned magnetite relics within the newly formed hematite caused a well-defined NW-SE trending magnetic lineation and steeper magnetic foliation. Later alteration associated with intense brittle deformation (stage II) initially adopted this magnetic fabric, but intense cataclasis destroyed it. The geometry and orientation of magnetic fabric clearly indicate a hydrothermal alteration, which relates to the acting tectonic stresses in the post-emplacement history of the Soultz granite.